A Shock Tube Study of Ethylene/Air Ignition Characteristics over a Wide Temperature Range. Issue 12 (1st December 2020) - Wan, Zhongjun; Zheng, Zujun; Wang, Yijun; Zhang, Dexiang; Li, Ping; Zhang, Changhua
ABSTRACT: As a key intermediate product, ethylene plays an important role in the combustion of heavy hydrocarbons. Very limited experiments have focused on the high temperature (>1000 K) ethylene ignition at the real fuel–air condition, but no one on the ethylene/air ignition at low temperatures (<1000 K). In the present work, ignition delay times of ethylene/air mixtures were measured at temperatures of 721 to 1307 K, pressures of 0.97 to 20.54 atm, and equivalence ratios of 0.5, 1.0 and 2.0，and ignition characteristics of ethylene/air were discussed. The high-temperature results show that ignition delay times decrease with the increase of temperature monotonously; the ignition delay of fuel-lean mixture exhibits an unusual behavior of almost zero pressure dependence, and stoichiometric and fuel-rich mixtures still have ordinary pressure dependence, with a pressure increase producing a decrease of ignition delay time. The results at wide temperatures indicate that ethylene/air ignition delay shows no negative temperature coefficient (NTC) behavior at low temperatures, and has an inflection point at the temperature of about 1000 K, showing a two-region ignition feature. The ignition delay times at two regions can be described by Arrhenius-type formulas, respectively, and the ethylene/air ignition delay is much less sensitive to the temperature at the low-temperature region. A good agreement is found between current data and another experimental data for high-temperature ignition. The mechanism used predicts the ethylene/air ignition delay well at high temperatures but must overpredict the ignition delay times at low temperatures. This work contributes to understanding the ethylene ignition properties at a wide temperature range and provides experimental data valuable for validating and refining the chemical kinetics mechanism of ethylene.